New species of Neomachilellus Wygodzinsky 1953 (Insecta: Archaeognatha: Meinertellidae) from Madre de Dios, Peru - Palacios-Martinez, Iñigo (Zootaxa, 2024)
This study describes a new species of jumping bristletail, Neomachilellus mercurialis sp. nov., discovered during a research expedition at the Los Amigos Biological Station in Madre de Dios, Peru. The specimens could not be morphologically assigned to any known species within the genus Neomachilellus s. str. Wygodzinsky 1953. Morphological examination revealed distinct differences in various characters, morphometric measurements, and pigmentation patterns compared to other species. The new species exhibits submedian, widened, oval-shaped ocelli, pigmentation on articles I‒VII of the maxillary palpi, and strong pigment on the femora, tibiae, and tarsi of the legs. Notably, femora and tibiae lack spines or prominent spiniform setae, while the tarsi feature spine-like setae characteristic of the nominal subgenus. The newly discovered species shares a close relationship with other taxa of Neomachilellus, specifically belonging to the muticus-group of species. Urgent taxonomic revision and molecular studies are warranted for this genus, emphasizing the ongoing challenges in understanding Archaeognatha.